Periopathogens in atherosclerotic plaques of patients with both cardiovascular disease and chronic periodontitis - Fazele Atarbashi-Moghadam; Seyed Rohollah Havaei; Seyed Asghar Havaei; Nafiseh Sadat Hosseini; Gholamreza Behdadmehr; Saede Atarbashi-Moghadam (ARYA Atherosclerosis, 2018)
BACKGROUND: Atherosclerosis and periodontitis are both chronic inflammatory diseases. Although a strong relationship between the two has already been established, the underlying mechanism is unknown. The present study was conducted aiming to detect the deoxyribonucleic acid (DNA) of Aggregatibacter actinomycetemcomitans (A.a), Campylobacter rectus (C.r), and Porphyromonas gingivalis (P.g) in subgingival and atherosclerotic plaques of patients with both chronic periodontitis and cardiovascular disease (CVD). METHODS: In this cross sectional study, patients with coronary artery disease (CAD) and moderate to severe periodontitis which were scheduled for coronary artery bypass grafting (CABG) were enrolled in the study. The subgingival plaques were collected before surgery. All samples were examined for the detection of selected periopathogens using polymerase chain reaction (PCR). RESULTS: The subgingival and atherosclerotic plaque samples of 23 patients were examined. The DNA of P.g, A.a, and C.r were found to be positive in 43.47%, 43.47%, and 78.26% of subgingival plaques, and 13.04%, 17.39%, and 8.69% of atherosclerotic plaques, respectively. In all cases, the bacterial species found in atherosclerotic plaques were also found in the subgingival plaques of the same patient. CONCLUSION: This study demonstrated the presence of periopathogens in atherosclerotic plaques of patients with chronic periodontitis. More studies are required to ascertain the exact role of these periopathogens in atherosclerotic plaque formation.